The Berenstain Bears and the blame game - Berenstain, Stan, 1923-2005; Berenstain, Jan, 1923-2012 (New York : Random House, 1997)
Members of the Bear family try to solve their problems without playing the blame game of arguing over who is responsible for every disaster.
Keywords: Responsibility -- Fiction; Behavior -- Fiction; Bears -- Fiction